Characterization of children and teenagers with ostomies in a health service (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objective: To characterize the socioeconomic and clinical profi le of children and adolescents with ostomies attended at a public reference hospital in children’s health in the state of Piauí, Brazil. Methods: Descriptive cross-sectional study of 55 children/adolescents with at least one ostomy. Results: There was a predominance of males, brown, mean age of 4.1 years. The main causes for the confection of the stoma were congenital malformations, especially the anomaly. Regarding the organic system, the gastrointestinal was the most aff ected and the colostomy was the most frequent. The majority of participants with elimination ostomies did not use collecting equipment. With regard to the complications of the stoma, the accidental release of the gastrostomy tube was the most common, followed by stomatal bleeding. Dermatitis was the most common skin complication. Conclusion: The realization of this study made it possible to know the socio-demographic profi le of children and teenagers with ostomies and to promote refl ections about nursing care to improve the assistance provided to these clients.
Keywords: Surgical ostomies; Hospitalized children; Nursing; Stomatherapy; Kid; Health profi le.